Revealing the stygobiont and crenobiont Mollusca biodiversity hotspot in the Caucasus: Part III. Revision of stygobiont microsnails (Mollusca: Gastropoda: Hydrobiidae) from the Russian part of Western Transcaucasia, with the description of new taxa - Chertoprud, Elizaveta M.; Palatov, Dmitri M.; Vinarski, Maxim V. (Zootaxa, 2021)
A taxonomic revision of the stygobiont microsnails from north-western Transcaucasia (Krasnodar Krai, Russia) is presented. Two new genera—Schapsugia gen. n. and Tachira gen. n. are established. It is shown that the genus Paladilhiopsis does not occur in this area, and the snails previously assigned to this genus belong to Schapsugia gen. n. Two nominal species Paladilhiopsis orientalis Starobogatov, 1962, and P. subovata Starobogatov, 1962 are considered junior synonyms of Sch. pulcherrima (Starobogatov, 1962), based on a re-examination of their conchological variation. In addition, two more species of Schapsugia are described: Sch. kudepsta sp. nov. and Sch. occultata sp. nov. The anatomical structure of another species, Geyeria valvataeformis Starobogatov, 1962 was studied for the first time. It is revealed that it should be placed in a separate genus (Tachira gen. n.). Thus, the previously proposed placement of the microsnails from north-western Transcaucasia in hydrobiid genera from the Balkan Peninsula (Geyeria, Paladilhiopsis) is rejected.